TESTING OF PROCESSING OIL WASTE TO BE BIODIESEL AS A FUEL ALTERNATIVE MOTOR DIESEL - Dwi Widjanarko; Abdurrahman Abdurrahman; Hadromi Hadromi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The objectives of this research are to desain and to test the biodiesel processing unit from waste cooking oil, to examine the characteristics of processed biodiesel, and to apply the biodiesel on diesel engine to ensure that there will not be a problem on the tested diesel engine. This research is an experiment research carried out by several steps, designing waste cooking-biodiesel processing unit, examining the characteristics ofbiodiesel made, and applying the biodiesel on diesel engine. The result showed that the biodtesel processing unit that was made could work well to produce biodiesel. The biodiesel characteristics are comparable with diesel oil and the biodiesel is applicable on diesel engine without any problems accured. Keywords: biodiesel, waste cooking oil, alternative fuel, diesel engine